Right ventricular function and outcome in patients undergoing transcatheter aortic valve implantation. (8th February 2021) - Koschutnik, M; Dannenberg, V; Nitsche, C; Dona, C; Siller-Matula, J; Winter, MP; Andreas, M; Bartko, P; Loewe, C; Aschauer, S; Anvari-Pirsch, A; Goliasch, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Right ventricular dysfunction (RVD) on echocardiography has been shown to predict outcomes in patients undergoing transcatheter aortic valve implantation (TAVI). However, a comparison with the gold standard, RV ejection fraction (EF) on cardiovascular magnetic resonance (CMR), has never been performed. Objectives. To compare RV function parameters on echocardiography and CMR for prognostication in TAVI patients. Methods. Consecutive patients scheduled for TAVI underwent echocardiography and CMR.  RV fractional area change (FAC), TAPSE, RV free-lateral-wall tissue Doppler (S') and strain were assessed on echocardiography, and RVEF on CMR. Patients were prospectively followed. Adjusted regression analyses were used to report the strength of association per 1-SD decline for each RV function parameter with 1) NT-proBNP levels, 2) prolonged in-hospital stay (>14 days), and 3) a composite of heart failure hospitalization and death. Results. 204 patients (80.9 ± 6.6y/o; 51% female; EuroSCORE-II: 6.5 ± 5.5%) were included. At a cross-sectional level, all RV function parameters were associated with NT-proBNP levels, but only FAC and RVEF were significantly associated with a prolonged in-hospital stay (adj. OR 1.98 [95%CI: 1.15-3.41], p = 0.013 and 2.29 [95%CI: 1.43-3.67], p = 0.001, respectively). A total of 56 events occurred during follow-up (mean 13.7 ± 9.5months). After adjustment for the EuroSCORE-II and NT-proBNP levels, only RVEF was significantly associated with the composite endpoint (adj. HR 1.69 [95%CI: 1.24-2.30], p < 0.001, Figure 1). Conclusions. RVD as defined by echocardiography is associated with an advanced disease state, but fails to predict outcomes after adjustment for pre-existing clinical risk factors in TAVI patients. In contrast, RVEF on CMR is independently associated with heart failure hospitalization and death.